A population specific mitochondrial intron from the sponge Phakellia robusta in the North-East Atlantic - Cranston, Alex; Taboada, S.; Koutsouveli, Vasiliki; Schuster, Astrid; Riesgo Gil, Ana (Deep Sea Research Part I: Oceanographic Research Papers, 2021)
Self-splicing mitochondrial introns are a rarely reported phenomenon in animals, with a sparse and uneven distribution confined to some species of sponges, corals, placozoans, and a single species of annelid. Here, we describe a mitochondrial intron present only in some populations of Phakellia robusta, a sponge distributed across the North-east Atlantic deep-sea. The mitochondrial intron of P. robusta was detected in the position 387 of the COI gene and classified as a Group I intron of class IB. Interestingly, this intron was only detected in the shallower populations of P. robusta from Ireland to Norway, spanning 1000 km and was absent in deeper samples of the species. Such deeper populations have recently been proposed to be the result of hybridization between P. robusta and its congeneric Phakellia hirondellei. We propose that this past hybridization might be behind the absence of the intron in the specimens of P. robusta occurring at deep waters. Our analyses indicate that the intron detected in P. robusta might have a double origin (most likely fungi and other organism), as it has previously suggested for the sponge Stupenda singularis. BLAST searches produced matches with the homing endonuclease gene (HEG) nested within the S. singularis intron and this HEG belongs to the family of LAGLIDADG homing endonucleases (LHEs). The evolutionary relevance of the presence/absence of this intron for this species needs to be determined and potential adaptive advantages should not be ruled out. This work was supported by the H2020 EU Framework Programme for Research and Innovation Project SponGES (Deep-sea Sponge Grounds Ecosystems of the North Atlantic: an integrated approach towards their preservation and sustainable exploitation) (Grant Agreement no. 679849). AS was further funded by Villum Fonden (Grant Agreement no. 16518). Peer reviewed